Variability of the SARS-CoV-2 Virus and the Susceptibility of the Population in the Dynamics of the Development of the Epidemic Process - I. V. Feldblum; M. Yr. Devyatkov; T.ёёё M. Repin; K. A. Subbotina; N. B. Voldshmidt; T. V. Shutova (Эпидемиология и вакцинопрофилактика)
Relevance. It is known that the main trigger for the development of the pandemic was the genomic diversity of viruses. Meanwhile, we did not find any studies on the influence of population susceptibility on the complex process of evolutionary transformations of the SARS-CoV-2 virus and their interdependent variability during the development of the pandemic. Aim. The study of the interdependent variability of two heterogeneous populations interacting in the dynamics of the development of the COVID-19 pandemic - the virus population and the population. Materials and methods. The study was conducted in the city of Perm from 03/01/2021. (Beginning of sequencing of the SARS-CoV-2 virus in the territory) until 01.01.2023. In weekly dynamics, the following were studied: SARS-CoV-2 genomic diversity (molecular genetic study of 2521 samples of biomaterial from patients), seroprevalence of the population (366,804 blood sera were examined for the presence of IgG), morbidity, disease prevalence rate and mortality (according to official statistics). The interpretation of the results was carried out in accordance with the provisions of the theory of self-regulation of parasitic systems by V.D. Belyakov. Results and discussion. An analysis of the genomic diversity of the virus during the pandemic made it possible to distinguish 5 periods. Three periods were characterized by the homogeneity of the pathogen population, when the variants Alpha, Delta and Omicron circulated. Two periods were characterized by the simultaneous circulation of two variants of viruses due to the adaptation of the virus to the changed habitat. Thus, the circulation of the Alpha variant in a population heterogeneous in terms of susceptibility (the proportion of seropositive ones increased to 52%) caused mutational changes in the virus genome with the formation of high transmission properties and high pathogenicity (according to the theory of V.D. Belyakov, the phase of formation of an epidemic variant). The formation of the epidemic variant of the pathogen (Delta genovariant) occurred within 12 weeks, it dominated for more than 6 months, increasing the incidence by 2.8 times, mortality by 17.3 times (epidemic spread phase). The increase in the incidence and large-scale vaccination increased the seroprevalence of the population to 70% or more. The Delta variant begins to adapt to a new habitat with a high proportion of immune organisms, the formation of the Omicron genovariant with high transmission and evasion of the immune response is underway (the phase of formation of the pathogen reservation variant). The pathogen population is heterogeneous; Delta and Omicron circulate simultaneously. Morbidity increases by 2.9 times, RT by 1.3 times, and mortality decreases by 5.1 times. Omicron replaces the Delta genovariant within 5 weeks, mortality decreases, while maintaining the distribution coefficient (reservation phase). Conclusions. Interdependent variability of the virus and the susceptibility of the population determined the phase development of the pandemic.